Prioritas Arahan Pemanfaatan Ruang Kawasan Sekitar Jalan Lingkar Ambarawa berdasarkan Potensi dan Limitasi - Pingkan Ellotama Tunjung Biru; Ragil Haryanto (Jurnal Wilayah dan Lingkungan, 2017)
The development of Ambarawa Ring Road leads to the increase of land conversion from vacant to the built-up area around. The study aims to analyze the spatial use priorities in Ambarawa Ring Road area based on the potentials and limitations by considering the experts’ perceptions. This study was conducted using a quantitative method of Analytical Hierarchy Process (AHP). The findings indicate that the spatial criteria are the main criteria for determining the spatial utilization in Ambarawa Ring Road. The weighted result for each sub-criterion that compares the potentials and limitations also shows that respondents prefer to prioritize the scenario to maintain the area around Ambarawa Ring Road as a vacant area. In addition, the alternative scenario reveals that the area around the Ambarawa Ring Road directed to developing tourism area while considering the environmental balance. Spatial planning plays a significant role in determining the direction of space utilization around Ambarawa Ring Road.